INVESTIGATING THE DETERMINANTS OF CASH WAQF INTENTION: AN INSIGHT FROM MUSLIMS IN INDONESIA - Masrizal Masrizal; Nurul Huda; Arridha Harahap; Budi Trianto; Tasiu Tijjani Sabiu (Journal of Islamic Monetary Economics and Finance, 2023)
This study looks at the factors that influence the Indonesian Muslim to perform cash waqf based on a modified Theory of Reasoned Action (TRA) framework. Using primary data from islands in Indonesia, as many as 436 respondents, and the partial least square approach, the paper finds that religiosity contributes positively to waqf literacy. Subject norms and religiosity also affect the attitude of Muslims in waqf. Religiosity is the most potent factor in influencing the attitude of Muslims in waqf. The variable of waqf literacy also affects the attitudes and intentions of Muslims in waqf. Finally, trust also affects the attitudes and intentions of Muslims in waqf.